Penjaminan mutu pendidikan dalam perspektif zonasi mutu - Irwan Fathurrochman (Jurnal Konseling dan Pendidikan, 2021)
The background of this research is the problem caused by the policy of the zoning radius system that regulates the admission of new students. The policy of this system cannot be denied that students who have achieved things are undervalued because they do not have the opportunity to study at the school of their choice. This results in a reduced student interest in learning. Based on this phenomenon, this study aims to: 1) determine the policy of implementing the zoning radius system; 2) determine the improvement of the quality of education with the policy of implementing the zoning radius system. This qualitative research uses interview, observation, and documentation data collection techniques. The collected data was then analyzed using only qualitative data analysis techniques. The location of this research is Madarasah Aliyah Negeri Rejang Lebong. The sources of data and informants selected were the principal, parents of students represented by the head of the school committee, and the teacher council. The results showed that the perspective of education with a zoning radius system was not very relevant to the location of Madrasah Aliyah Negeri Rejang Lebong in particular, because many students had difficulty accessing the best educational services. Education must be accessible to all people, regardless of the student's location of origin and be non-discriminatory in providing services.